2008
DOI: 10.1002/anie.200803834
|View full text |Cite
|
Sign up to set email alerts
|

Topographically Flat, Chemically Patterned PDMS Stamps Made by Dip‐Pen Nanolithography

Abstract: Flexible nanolithographic and printing methods are essential tools in the field of nanoscience and nanotechnology. [1][2][3][4][5] Scanning probe techniques such as dip-pen nanolithography (DPN) [3,[6][7][8][9][10][11][12] and nanografting [13,14] are extremely useful since they allow one to make nanostructures from a wide variety of different chemical compositions. In the case of DPN, despite significant advances in parallelization, [2,[15][16][17] it is still challenged for certain applications with regard t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 45 publications
0
37
0
Order By: Relevance
“…Reproduced with permission. [ 29 ] D) Optical image of an array of arbitrary photoresist patterns fabricated with PEG phase-shift lenses. The AFM image to the right shows that the letter "N" consists of well-shaped features.…”
Section: Polymer Resists For Nanofabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…Reproduced with permission. [ 29 ] D) Optical image of an array of arbitrary photoresist patterns fabricated with PEG phase-shift lenses. The AFM image to the right shows that the letter "N" consists of well-shaped features.…”
Section: Polymer Resists For Nanofabricationmentioning
confidence: 99%
“…[ 28 ] In another example, Zheng et al fabricated PEG nano structures with DPN on fl at PDMS as a resist for plasma treatment. [ 29 ] After backfi lling of various silane molecules on the unprotected areas and removal of the PEG resist, a topographically fl at PDMS stamp with well-defi ned chemical regions was formed, which could be used for microcontact printing of small molecules, proteins and polar inks at sub-100 nm. Furthermore, since DPN-deposited PEG dots on glass are hemispheric and transparent, they possess optical properties and can be employed as nanosized lenses for subwavelength photolithography: [ 30 ] parallel light passing through PEG was focused beneath the center of the PEG lens, with a lower intensity at the edges.…”
Section: Polymer Resists For Nanofabricationmentioning
confidence: 99%
“…If the feature aspect ratio on the stamp is not between 0.2 and 2, bending of the stamp can cause pattern defects, and, for features that are too widely separated (>0 h ), sagging of the stamp causes defects. Indeed, the fabrication of alkanethiol features smaller than 150 nm is a significant challenge using conventional methods 44 . By using DPN to introduce chemical modifications on a flat PDMS stamp and by passivating the surrounding areas with a perfluorinated monolayer, we have helped overcome this deficiency, and shown that features as small as 80 nm could be easily prepared with aspect ratios as low as 0.01.…”
Section: High-throughput Molecular Printing With Soft Lithographymentioning
confidence: 99%
“…Microcontact printing of 1-hexadecanethiol on gold slides and subsequent chemical etching 26 Glass slides were soaked in 1 : 3 volume ratio of H 2 O 2 /H 2 SO 4 solution for at least an hour and thoroughly rinsed with 18 MU H 2 O, ethanol and dried under a stream of nitrogen. Cleaned glass slides were used for depositing chromium as the adhesion layer followed by gold deposition inside a thermal evaporator.…”
Section: Scanning Electrochemical Microscopy Of Pdms Stampmentioning
confidence: 99%